MENJAGA KESEIMBANGAN ANTARA KEBEBASAN EKSPRESI DAN PERLINDUNGAN PUBLIK: TINJAUAN HUKUM TERHADAP LARANGAN UJARAN KEBENCIAN DAN BERITA BOHONG DI INDONESIA - Gunawan Widjaja (ADISAM PUBLISHER, 2026)
This article analyses how Indonesian law maintains a balance between freedom of expression and public protection in the context of prohibiting hate speech and fake news. Using a normative-juridical literature review approach, this study examines legal instruments such as the 1945 Constitution, the Electronic Information and Transactions Law, the Criminal Code, and relevant decisions of the Constitutional Court and other courts. The results show that the regulation of hate speech and fake news does aim to protect vulnerable groups and maintain public order, but the multi-interpretable provisions and repressive law enforcement have the potential to stifle critical expression and have a chilling effect on public participation. The main implications and challenges lie in the need for restrictions on freedom of expression that meet the principles of necessity and proportionality, as well as a combination of a criminal law approach with the strengthening of digital literacy, human rights education, and the active involvement of civil society and digital platforms. In conclusion, an ideal balance can only be achieved through clearer regulations, fair and transparent law enforcement, and the development of a critical and responsible public culture in the digital space.